Analysis of The Relationship Between The Contact History of Patients Suspected for Covid-19 and Psychological Disorders in Nurses at Hospital X, Demak District - Octarini, Dewi; Yuniastuti, Ari; Azam, Mahalul (Universitas Negeri Semarang, 2025)
The aim of this inquiry was to examine the relationship between contact history with suspected COVID-19 patients and the level of psychological distress among nurses at Hospital X, Demak Regency. A retrospective survey was conducted involving 60 nurses, representing the entire nursing population at the hospital. The analysis showed that contact history with suspected COVID-19 patients was associated with depression. The P-value is 0.008, the anxiety level shows a P-value of 0.004, the stress level shows a P-value of 0.0027, PTSD shows a P-value of 1.000. The results of the analysis show that there is a significant relationship, namely anxietyas many as 62.5% experienced moderate anxiety. Nurses in the Emergency Department showed a high rate of PTSD, at 41.7%. Furthermore, factors such as gender, age, and length of service were also statistically associated with contact history with suspected COVID-19 patients. A statistical analysis revealed a significant correlation between contact history with suspected COVID-19 patients and PTSD levels in nurses. These findings provide important insights into the potential psychological impact on nurses who have had contact with suspected COVID-19 patients. In the real world, this research can help develop plans to support nurses' mental well-being during the pandemic.